Plant diversity in suburban Mediterranean ecosystems: The case of “Sheikh Sou”, Thessaloniki, Greece - Papadimitriou M.; Sklavou P.; Atskakani M.E.; Sidiropoulou A.; Chouvardas D. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Mediterranean ecosystems have traditionally developed through human intervention. Especially the ones located near urban areas, have been imposed to various changes resulting from restoration practices such as reforestation, land use change, fire etc. effecting vegetation structure and diversity. The aim of this paper was to study the effects of various human-caused perturbations on plant cover and species diversity and composition in suburban Mediterranean ecosystems. The research was conducted in the “Sheikh Sou” suburban park of Thessaloniki, North Greece. Three different human-caused perturbations have occurred in the suburban ecosystem of “Sheikh Sou” represented by: i) abandoned arable field ii) postfire natural revegetation and iii) pine plantation. Plant cover was recorded on three experimental sites using the line point method and species richness, Shannon-Wiener diversity index and evenness were calculated. The three experimental sites had high plant cover; however the dominant plant group differed among the experimental sites. Abandoned arable field appeared higher plant diversity and evenness, while postfire natural revegetation and pine plantation had vertical plant stratification. Our results suggest that human-caused perturbations in suburban Mediterranean ecosystems affect differently the structure of the plant community and species diversity. In suburban Mediterranean ecosystems proper management actions should be taken in order to preserve a diverse mosaic of vegetation types.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)